Minsky at Basel: A global cap to build an effective postcrisis banking supervision framework - Giuseppe Mastromatteo; Lorenzo Esposito (Levy Economics Institute of Bard College, 2016)
The global financial crisis shattered the conventional wisdom about how financial markets work and how to regulate them. Authorities intervened to stop the panic-short-term pragmatism that spoke volumes about the robustness of mainstream economics. However, their very success in taming the collapse reduced efforts to radically change the "big bank" business model and lessened the possibility of serious banking reform-meaning that a strong and possibly even bigger financial crisis is inevitable in the future. We think an overall alternative is needed and at hand: Minsky's theories on investment, financial stability, the growing weight of the financial sector, and the role of the state. Building on this legacy, it is possible to analyze which aspects of the post-2008 reforms actually work. In this respect, we argue that the only effective solution is to impose a global cap on the absolute size of banks.
Keywords: E12; G01; G28; 330; Banking Regulation; Financial Stability; Minsky; Basel 3